Dynamic spreading of re-melted volcanic ash bead on thermal barrier coatings. (1st July 2020) - Yang, Shanjie; Song, Wenjia; Lavallee, Yan; Zhou, Xin; Dingwell, Donald B.; Guo, Hongbo
Graphical abstract: Highlights: Dynamic spreading of volcanic ash on thermal barrier coating were investigated. Subsurface lateral flow can be observed accompany with spreading and infiltration. Spreading controlled by melt viscosity, coating surface roughness and microstructure. Spreading process was divided into 3 stages and the impact factors were discussed. Abstract: Dynamic spreading of 1 mm diameter volcanic ash bead on thermal barrier coatings (TBCs) surfaces and the infiltration and subsurface lateral flow of these melts within TBCs were quantitatively investigated at 1200−1600 °C for 1−10000 min. The spreading areas, infiltration depths and lateral flow distances are controlled by melt viscosity, coating surface roughness and microstructures. The lateral flow along the inter-column of the coating was dramatically accelerated at higher temperature with a diffusion distance of more than 5.3 mm within 1 min at 1600 °C. These findings are critical for understanding the corrosion mechanism of TBC in contaminated environments.